The five principles of middle way philosophy: living experientially in a world of uncertainty - Ellis, Robert M. (Middle way philosophy, 2023)
"This second book in the 'Middle Way Philosophy' series develops five general principles that are distinctive to the universal Middle Way as a practical response to absolutization. These begin with the consistent acknowledgement of human uncertainty (scepticism), and follow through with openness to alternative possibilities (provisionality), the importance of judging things as a matter of degree (incrementality), the clear rejection of polarised absolute claims (agnosticism) and the cultivation of cognitive and emotional states that will help us resolve conflict (integration)"--